Stress and Coping Mechanisms among nursing students in Kathmandu - Bista, B; Bhattrai, B; Khadka, N (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
Background: Every person experiences different forms of stress throughout their life. Therefore a student nurse is no exception as they have to adjust to an entirely new environment on joining nursing. Stress in nursing students is an area of growing concern. The stress among the students can have serious effects on their health and studies. It may affect in psychological distress, physical complains, behavior problems and poor academic performance.Objective : The main objective of this study was to assess the level of stress and coping mechanisms among nursing students.Methodology: A descriptive cross-sectional study was done among 283 nursing students of Manmohan Memorial Institiute of Health Sciences (MMIHS), by using purposive sampling technique. The level of stress was assessed using Perceived stress scale-14 (PSS-14) and coping mechanism was assessed using Brief cope inventory. The data analysis was done using SPSS version 20.  Descriptive and inferential statistics was used and Chi-square test was applied for association.Result: The results were found that 61.5% of the respondents have moderate stress and 27.9% of the respondents have severe stress and mild stress only by 10.6%.Likewise 44.5% of the respondents were very often stressed due to test, examination and evaluations where as half of the majority of respondents were some time deal with dying or seriously ill patient.  Similarly 58.3% used Emotion-focused strategies for coping mechanism and 3.9% of the respondents used Problem-focused strategies for coping mechanism.Conclusion: Majority of the nursing students were found to have moderate stress. Perceived stress scale was found to be statistically significant with age, educational status of the respondents, education of father and mother. Majority of the respondents used emotion-focused strategies for coping and minority of the respondents used problem-focused coping strategies.Journal of Manmohan Memorial Institute of Health SciencesVol. 3, No. 1, 2017, page:16-23